The ILO Standards and Canadian Labour Legislation - Zeytinoglu, Isik (Relations industrielles / Industrial Relations, 1987)
The author analyzes the impact of the International Labour Organization 's Freedom of Association Standards on Canadian labour legislation in the last decade.